FROM EFL TO EMI: A CASE OF THAI INTERNATIONAL STUDENTS’ L2 LEARNING MOTIVATION AND ENGAGEMENT IN CHINA - Prapunta, Sudatip (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study aims to explore Thai international students’ attitudes towards teaching approaches maximizing their second language (L2) learning motivation and engagement and the motivating and demotivating factors influencing their L2 learning experiences during the transition from EFL to EMI contexts. The participants, selected by the purposive sampling method, were five senior Business English major undergraduates in southern Thailand who were enrolled as international students in a Chinese multilingual university for two semesters. Semi-structured interviews were employed, and qualitative data was inductively analyzed using thematic analysis. The findings indicated that all participants felt motivated and engaged to take the English for International Business and Trade course within the field of Content and Language Integrated Learning (CLIL) in the EMI Business Program. They tended to sustain their intended effort to complete communicative-based tasks and term projects related to their future professional goals, acquire specialized business knowledge, and develop digital literacy skills. Despite experiencing fluctuating motivation and transitional challenges, they reported their native-speaker teacher helped them reduce their constraints regarding English language use by editing their writing tasks and presentation scripts. Furthermore, they developed their English language proficiency, L2 self-confidence, and intercultural competence. These findings illuminate several factors influencing the student sojourners’ L2 learning motivation and engagement in EMI settings. The study sheds light on the pedagogical implications of implementing practical courses and developing the instructional quality of the curriculum in internationalized higher education institutions.